2006
DOI: 10.1194/jlr.m500468-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-phosphate is released from the cytosol of rat platelets in a carrier-mediated manner

Abstract: Sphingosine 1-phosphate (S1P) is accumulated in platelets and released on stimulation by thrombin or Ca 21 . Thrombin-stimulated S1P release was inhibited by staurosporin, whereas Ca 21 -stimulated release was not. When the platelet plasma membrane was permeabilized with streptolysin O (SLO), S1P leaked out with cytosol markers, whereas granular markers remained in the platelets. The SLOinduced S1P leakage required BSA, probably for solubilization of S1P in the medium. These results indicate that S1P is locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
135
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(143 citation statements)
references
References 44 publications
8
135
0
Order By: Relevance
“…5A). Consistent with the previous report (Kobayashi et al, 2006), glyburide also inhibited the thrombin-dependent release of endogenously generated S1P (Fig. 5B).…”
Section: Two Fty720-p Transporters Exist In Plateletssupporting
confidence: 81%
See 2 more Smart Citations
“…5A). Consistent with the previous report (Kobayashi et al, 2006), glyburide also inhibited the thrombin-dependent release of endogenously generated S1P (Fig. 5B).…”
Section: Two Fty720-p Transporters Exist In Plateletssupporting
confidence: 81%
“…The involvement of an ATP-binding cassette (ABC) transporter in stimulus-dependent S1P release from platelets has been suggested, since ATP is required, and the ABC transporter inhibitor glyburide/glibenclamide inhibited the release (Kobayashi et al, 2006).…”
Section: Two Fty720-p Transporters Exist In Plateletsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies from several laboratories, including ours, have suggested the involvement of ABC transporters in S1P export from mast cells (32), platelets (33), endothelial cells (34), astrocytes (35), thyroid follicular cell (45), fibroblasts (46), and erythrocytes (47). Similarly, using pharmacological and molecular approaches, we demonstrated that ABCC1 and ABCG2 are involved in E 2 -mediated transport of S1P and dihydro-S1P out of MCF-7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…ABCC1 and ABCG2 Mediate E 2 -induced Export of S1P-Recent studies suggest that members of the ABC transporter family might be involved in release of S1P from several types of cells (32)(33)(34)(35). Three ABC transporters, ABCB1 (also known as multidrug resistant gene 1 (MDR1)) or p-glycoprotein, ABCC1 (also known as multidrug resistance protein 1 (MRP1)), and ABCG2 (also known as breast cancer resistance protein), appear to account for 80 -90% of multidrug-resistant human tumor cells (36).…”
Section: Er-␣ But Not Gpr30 Is Required For E 2 -Mediated Rapidmentioning
confidence: 99%